2022
DOI: 10.1111/epi.17242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self‐reported emotional, physical, and sexual abuse and association with fear of childbirth in pregnant women with epilepsy: The Norwegian Mother, Father, and Child Cohort Study

Abstract: Objective: This study was undertaken to examine the prevalence of self-reported experiences with abuse in pregnant women with epilepsy and the association between having experienced abuse and childbirth expectations, particularly the fear of childbirth. Methods:We performed a cross-sectional study of women with and without epilepsy enrolled in the Norwegian Mother, Father, and Child Cohort Study 1999-2008. Data on epilepsy diagnosis; antiseizure medication (ASM) use; emotional, physical, and sexual abuse; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although there have been many publications on seizure control in pregnancy, there is limited information on how other aspects of WWE's pregnancy experience are distinct. Other studies demonstrated that pregnant WWE were more likely to report lower self-esteem and life satisfaction as well as higher rates of abuse, 8,9 but this is the first to examine a broad range of specific stressors. Another strength of this study is its large sample size, which represents several states across the United States.…”
mentioning
confidence: 89%
“…Although there have been many publications on seizure control in pregnancy, there is limited information on how other aspects of WWE's pregnancy experience are distinct. Other studies demonstrated that pregnant WWE were more likely to report lower self-esteem and life satisfaction as well as higher rates of abuse, 8,9 but this is the first to examine a broad range of specific stressors. Another strength of this study is its large sample size, which represents several states across the United States.…”
mentioning
confidence: 89%
“…The bad news gets worse. Vederhus et al 5 included ∼600 pregnant WWE and ∼90 000 pregnant women without epilepsy (WWoE) in a Norwegian cohort 1998-2008 that linked survey responses to national registry data. Forty-seven percent of pregnant WWE versus 32% of pregnant WWoE reported any emotional, physical, or sexual abuse, and 11% versus 4% reported a history of rape.…”
Section: Commentarymentioning
confidence: 99%